Youth and e-commerce purchasing trends. - Pérez Fernández, Alberto; Martínez Luis, David; Torres Tello, Giovanna Patricia (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2025)
OBJECTIVE: To identify the most frequently purchased products and the most significant factors considered by young people when making purchases on e-commerce platforms.MATERIAL AND METHOD: This is a descriptive and exploratory study. A total of 313 young people from a sample at the School of Economic-Administrative Sciences at the Autonomous University of Carmen were included.RESULTS: 94% of young people have made a purchase on an e-commerce platform. However, 47% of them make a purchase with the insecurity that the product they ordered online may not arrive. The products they buy the most are clothing, electronic devices, and cosmetics. The variables they consider when choosing a product online are the price, the product description, and the image. Among purchasing trends, gender was not observed to be a determining factor in online purchases.CONCLUSIONS: Young people are more involved with social networks and participate more in online shopping. New market structures compel companies to modify their distribution channels and the products they offer to address new forms of purchasing through e-commerce.
Keywords: consumers; demand for goods; online shopping.